Systemic Regulatory T Cells and IL-6 as Prognostic Factors for Anatomical Improvement of Uveitic Macular Edema - Matas, Jessica; Llorenç, Victor; Fonollosa, Alex; Díaz-Valle, David; Esquinas, Cristina; de la Maza, Maria Teresa Sainz; Figueras-Roca, Marc; Artaraz, Joseba; Berasategui, Barbara; Mesquida, Marina; Adán, Alfredo; Molins, Blanca (Frontiers in Immunology, 2020)
Purpose To investigate whether systemic immune mediators and circulating regulatory T cells (Tregs) could be prognostic factors for anatomic outcomes in macular edema secondary to non-infectious uveitis (UME). Methods Multicenter, prospective, observational, 12-month follow-up study of 60 patients with UME. Macular edema was defined as central subfield thickness (CST) > 300 μm measured with spectral domain optical coherence tomography (SD-OCT). Serum samples and peripheral blood mononuclear cells (PBMC) were obtained from venous blood extraction at baseline. Serum levels of IL-1β, IL-6, IL-8, IL-17, MCP-1, TNF-α, IL-10, and VEGF were determined by Luminex. Tregs population, defined as CD3+CD4+FoxP3+ in PBMC, was determined by flow cytometry. Main outcome measure was the predictive association between searched mediators and CST sustained improvement, defined as CST < 300 microns or a 20% CST decrease, at 6 months maintained until 12-months compared to baseline levels. Results Multivariate logistic regression analysis showed an association between CST sustained improvement at 12 months follow-up and IL-6 and Tregs baseline levels. Higher IL-6 levels were associated with less events of UME improvement (OR: 0.67, 95% CI (0.45–1.00), P = 0.042), whereas higher levels of Tregs favored such improvement (OR: 1.25, 95% CI: 1.12–2.56, P = 0.049). Conclusions Increased levels of Tregs and reduced levels of IL-6 in serum may be prognostic factors of sustained anatomical improvement in UME. These findings could enforce the opportunity to develop more efficient and personalized therapeutic approaches to improve long-term visual prognosis in patients with UME.